Efficiency of laser-induced desorption of D from Be/D layers and surface modifications due to LID. (24th June 2020) - Zlobinski, Miroslaw; De Temmerman, G; Porosnicu, C; Matveev, D; Unterberg, B; Sergienko, G; Brezinsek, S; Nicolai, D; Terra, A; Rasinski, M; Spilker, B; Freisinger, M; et al.
Abstract: For the in situ application of LID (Laser-Induced Desorption) as a space-resolved tritium retention diagnostic in ITER, the desorption behaviour of co-deposited deuterium (D) from beryllium (Be) layers is studied. In particular, the desorption efficiency dependence on laser pulse parameters is investigated for pulse durations of 1–20 ms and absorbed energy densities up to 5 MJ m −2 . For these parameter scans homogenous Be/D layers were produced by High Power Impulse Magnetron Sputtering, with 10 μ m thickness and 1.6 at% D. Almost 99% of the initial D can be desorbed with a single LID pulse. As the layers show a high D desorption temperature (ca. 800 K) in slow Thermal Desorption Spectrometry, an LID efficiency of only 50% is reached before Be melting. Microscopy reveals that in molten regions holes are formed, which could serve as desorption channels to facilitate gas release above the melting point. Hill formation and cracking are further modifications, but no layer destruction was observed in general.